The occurrence of Ehrlichia ruminantium and other haemoparasites in calves in western Kenya determined by reverse line blot hybridization assay, real-time PCR and nested PCR - Collins, Nicola E. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.